Wellens’ Sign (Wellens’ Syndrome) - Jonathan Patane; Kim Sokol (Journal of Education and Teaching in Emergency Medicine, 2017)
History of present illness: This was a 65-year-old male who had no significant past medical history, who presented to the emergency department with numbness to his left face and left upper and lower extremities. He had these symptoms for two days, but did not seek medical attention. He denied chest pain or shortness of breath. As part of his workup, he had an EKG performed, which is shown below.